Spatio-temporal Patterns Evolution of Coupling Coordination of Ecosystem Services and New Urbanization in the Beijing-Tianjin-Hebei Region - Zhang, Yujing (Transactions on Environment, Energy and Earth Sciences, 2024)
Clarifying the coupling coordination relationship between ecosystem services and new urbanization is of great significance for promoting high-quality and sustainable development in the region. In this study, 197 county administrative units in the Beijing-Tianjin-Hebei region were selected as the study area, and the ecosystem service value index and new urbanization level from 2005 to 2020 were calculated respectively. The coupling coordination degree model was used to analyze the spatial-temporal correlation pattern evolution of the coupling coordination degree between the two. Results show that: ① The ecosystem service value index in the Beijing-Tianjin-Hebei region first decreased and then increased, showing an overall upward trend, manifested as a spatial pattern of "high in the north and low in the south, high in the west and low in the east", with different spatial distribution patterns of sub ecosystem services; ② The overall level of new urbanization is showing a continuous upward trend, manifested by a spatial pattern from "high in the north and low in the south" to "high in the north and south, low in the middle". ③ The coupling coordination degree shows a steady upward trend, but overall it is in a stage of mild imbalance, manifested as a spatial pattern of "high in the north and low in the south".